Partisipasi Politik Warga Negara Dalam Perspektif Kewarganegaraan Politik Pada Pemungutan Suara Ulang Pemilihan Wali Kota Banjarbaru Tahun 2025 - M. Ridhai; Wardiani Hiliadi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to describe the political participation of citizens from the perspective of political citizenship in the implementation of the Revote (PSU) for the 2025 Banjarbaru Mayoral and Deputy Mayoral Elections, viewed from the perspective of public political awareness. The implementation of the PSU is a follow-up to the Constitutional Court's decision to annul the results of the 2024 Banjarbaru Mayoral Election.. Research informants were determined using a purposive sampling technique that included the community as voters, KPU Commissioners, PPK, PPS, KPPS, Lurah, and RT. The results of the study indicate that the people of Banjarbaru City have good political awareness in exercising their right to vote as a form of implementing the rights and obligations of citizens in a democratic life. However, the level of public participation in the 2025 PSU has decreased. This decline was influenced by the views of some people who consider clerics or religious figures as role models and considerations in determining political attitudes regarding female leadership (patriarchy), so that some people chose the empty box or did not use their voting rights (golput) in the implementation of the 2025 PSU.